Effect of stroke-order learning and handwriting exercises on recognizing and writing Chinese characters by Chinese as a foreign language learners. (September 2017) - Hsiung, Hsiang-Yu; Chang, Yu-Lin; Chen, Hsueh-Chih; Sung, Yao-Ting
Abstract: This study used a computer-based teaching system to investigate the effectiveness of stroke-order learning and writing exercises in promoting the ability of Chinese-as-a-foreign-language (CFL) learners to recognize and write Chinese characters. This study included a 2 (stroke-order and non-stroke-order) × 2 (writing exercise and non-writing exercise) × 2 (test point) mixed factorial design involving a total of 91 participants. We compared the difference in their Chinese character learning, including Chinese character recognition and handwriting, based on the learning conditions. We found that CFL learners who practiced writing the characters had improved accuracy in their Chinese writing assignments and meaning assignments compared with students who did not practice writing, indicating that writing exercises helped students to memorize the orthography and output of Chinese characters. Writing exercises also helped improve memorization of the meaning of Chinese characters. However, the traditional emphasis on the correct stroke order, which has been considered helpful for learning Chinese characters, demonstrated no significant impact on the effectiveness of recognizing and writing Chinese characters. Highlights: Examining the learning effect of stroke-order learning and writing exercises. The results supports the effect of writing exercise on learning Chinese characters. Stroke order learning did not improve the recognition of Chinese characters.